Problem gambling and concurrent emotional/behavioral problems among Greek adolescents - Paleologou, Assimina (Turk Pediatri Ars, 2019)
AIM: Problem gambling in adolescents constitutes a major health problem. Very few studies have investigated the relationship of adolescent gambling with emotional/behavioral problems. The aim of this study was to examine the association between adolescent problem gambling and emotional/behavioral problems using data from a school survey in the greater Athens area. MATERIAL AND METHODS: The total sample consisted of 2159 high school students (45.4% males and 54.6% females) from a random and representative sample of public and private schools in the greater Athens area. Data were collected in the form of self-reported questionnaires during one school hour. To access problem gambling the Diagnostic and Statistical Manual of Mental Disorders-IV Multiple Response Adapted for Juveniles questionnaire was administered to the study population. The presence of emotional/behavioral problems was assessed via the Strengths and Difficulties Questionnaire. Full data from 2141 participants were analyzed. Eighteen questionnaire with incomplete data were excluded. RESULTS: Problem gambling in adolescence is in line with the presence of emotional/behavioral problems. All Strengths and Difficulties Questionnaire subscales were significantly associated with problem gambling. Specifically, emotional symptoms, conduct problems, attention/hyperactivity, and social dysfunction were all significantly and independently associated with adolescent pathologic gambling. The prosocial scale had lower scores in problem gamblers. CONCLUSION: This article aims to highlight and discuss the coexistence of adolescent problem gambling with other symptoms. The significant association of emotional/behavioral problems among adolescents with problem gambling indicates a need to screen for these symptoms and for their subsequent treatment among adolescents with problem gambling.